PRINCIPLES OF IMPLEMENTATION OF FINANCIAL LITERACY AT BMT ALMABRUK BATUSANGKAR BASED ON SE OJK NUMBER 30/SEOJK.07/2017 - Elmiliyani Wahyuni S; Ginta Dwi Lestari (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
The purpose of this study is to find out the principles of implementing financial literacy in BMT based on SEOJK Number 30/SEOJK.07/2017. This type of research is a field research with a qualitative approach. The results showed that the principle of implementing financial literacy carried out by BMT Almabruk Batusangkar was based on SEOJK regulations Number 30/SEOJK.07/2017, namely planned and measurable, optimizing existing resources, and sustainable, not yet collaborating with stakeholders. The strategy for implementing the financial literacy function or unit at BMT Almabruk is through direct socialization to customers and prospective customers, as well as, through indirect socialization, namely through print and electronic media. Meanwhile, the obstacles and challenges faced are human resources who are not yet competent in their fields, as well as the lack of product innovation and limited technological facilities.